A microgovernança de redes público-privadas e a geração de ganhos relacionais: estudos de casos em comitês de bacias hidrográficas - Bertolini, Olívia Trevisani (Universidade do Vale do Rio dos Sinos, 2020)
The complexity of enviromental, economics and social problems haschanged the relationship between the state and organized civil society, which translates into the elaboration and implementation of public policies by means of interorganizational networks, composed by public and private actors, and the governance of the networks is decisive for generating relational gains. This study sought to understand how the functions and mechanisms of micro-governance in the public-private network are used and the gains obtained. A qualitative exploratory survey was carried out, withthe comparative analysis of two Hydrographic Basin Committees: Comitesinos and Pardo Committee. The Basin Committees are coordinatedby public and private actors, with the aim of guaranteeing quality and quantity of water for human use and industry, thus generating a reflection on the health of the population and on economic activities. The collection of data included semi-structured interviews, documentary analysis and non-participating observation. The evidence points to the importance of aligning and integrating participants, including networks in which formalization is inherent, since they are instituted by law. Relational gains linked to public value and knowledge were highlighted in both committees. This study contributes to the advance of network analyzes under its internal mechanisms (micro-governance) and in the identification of relational gains in public-private networks. On the managerial dimension, information is available to public and private managers that can support corrective actions in the governance of interorganizational networks or in the development and implementation of public policies.
Keywords: Governança; Ganhos relacionais; Redes público-privadas; Comitês de Bacia; Governance; Relational gains; Public-private networks; Basin committees; ACCNPQ::Ciências Sociais Aplicadas::Administração